Wide Anterior Maxillary Reconstruction with Equine Bone Xenograft: A Case Report of 24-Month Follow-Up - Davide De Cicco; Giuseppe Colella; Gianpaolo Tartaro; Nicola Zerbinati; Romolo Fragola; Raffaele Rauso (Case Reports in Surgery)
Introduction. Orofacial reconstruction plays an important role in the treatment of patients affected by oral and maxillofacial cancers. Improvements in technologies and studies of biomaterials have widely expanded surgical possibilities to achieve good functional and aesthetic outcomes. By the way, xenografting procedures gained great consensus in the last decades, because of their documented reliability and efficacy. We present a case of anterior maxillary chondrosarcoma (CHS) that has undergone surgical ablation followed by reconstruction with an equine-derived bone xenograft. Case Presentation. A 68-year-old woman affected by CHS of the premaxilla underwent surgical ablation involving the four incisors followed by reconstruction using an equine-derived bone substitute. Bony reconstruction was planned to achieve implant and dental prosthetic rehabilitation at a second surgical time. Primary surgery was carried out without complications. Good integration of the graft was confirmed by radiological examination. At 12-month follow-up, the patient refused the implant placement and spontaneously adopted a mobile prosthesis. One year later, plates and screws were removed, because of the exposure of a titanium plate. The graft was finally rejected within 3 weeks. Discussion. Nonantigenic equine-derived biomaterials have shown reliability and a good safety profile. In the presented case, implant insertion should have been performed 12 months after the primary surgery. During the follow-up, until dental mobile prosthesis was applied, clinical and instrumental examinations demonstrated a good integration of the graft. We suppose that a chronic inflammation of the mucosa led to the exposure of the plate, perhaps due to pressure, minimal movements, or imperfect fitting of the mobile prosthesis. Removal of fixation means was performed to prevent grafting failure, without success. On the other hand, missing load could induce the graft to act just like a prosthesis, without a real process of integration. Safety and reliability of equine-derived bone xenografts cannot be currently confirmed if not followed by implant insertion and dental rehabilitation.